Efeito da LED terapia em modelo experimental de fibrose pulmonar - Brochetti, Robson Alexandre (2016)
Pulmonary fibrosis (PF) is a chronic and progressive lung disease characterized by pulmonary parenchyma progressive lesion, inflammatory infiltration, and interstitial fibrosis. It is developed by excessive collagen deposition and other cellular matrix components, resulting in severe changes in the alveolar architecture. Considering the absence of effective treatment, the aim of this study was to investigate the effect of LED treatment on the development of PF. For this purpose, we used C57BL/6 mice submitted to induction of PF by bleomycin administration (1.5 U / kg) by orotracheal route and, after 14 days of the induction, mice were treated with LED once daily for 8 days. It was evaluated inflammatory and fibrotic parameters with or without LED treatment. Our results showed that treatment with LED significantly reduced the number of inflammatory cells in the alveolar space, collagen production, interstitial thickening, and static and dynamic pulmonary elastance. In addition, we observed reduced levels of IL-6 e CXCL1/KC released by pneumocytes type II in culture as well as reduced level of CXCL11/KC released by fibroblasts in culture. It can be concluded that the LED therapy improved both inflammatory and fibrotic parameters and, it can be a promisor therapy with low cost and absent of side effects.